Optimizing Human Resources For Public Service Quality: Optimalisasi Sumber Daya Manusia dalam Meningkatkan Kualitas Layanan Publik - Lola Astrid Pradina; Sintania Fanissa Asrori; Andhika Ayu Luthfiyani; Muhammad Anugerah Ramadhan; Abdul Mughni (International Consortium of Education and Culture Research Studies, 2025)
General Background Public service delivery represents a core governmental function for guaranteeing societal welfare and reflecting state presence in fulfilling basic needs. Specific Background Within regional governance contexts, the Bureau of Economic Administration holds a vital role in supporting regional economic policy coordination and implementation. Knowledge Gap Despite existing capacity-building initiatives, bureaucratic optimization frequently confronts critical challenges regarding uneven training distribution, digital adaptation hurdles, and rigid organizational cultures. Aims This study analyzes how human resource optimization improves public service quality at the Bureau of Economic Administration of the East Java Provincial Secretariat. Results Findings demonstrate that staff optimization significantly drives service delivery performance across developmental, knowledge, attitudinal, behavioral, and competency indicators, though structural obstacles persist. Novelty This research specifically evaluates internal bureaucratic optimization through five core administrative dimensions combined with empirical field observations in regional secretariats. Implications Public institutions must implement sustainable strategies including competency-based training, digital service integration, and robust reward systems to ensure professional and citizen-oriented governance. Highlights: Competency-based training initiatives and digital integration are essential for overcoming uneven administrative capacity-building programs across regional bureaus. Rigid hierarchical bureaucratic cultures and inadequate reward systems constrain employee motivation and proactive service innovation. Staff optimization directly improves public service reliability, responsiveness, and professional accountability within regional economic governance. Keywords: Human Resource Optimization, Public Service Quality, Bureaucratic Administration, Regional Secretariat, Governance Performance